Effects of calcitonin, risedronate, and raloxifene on erythrocyte antioxidant enzyme activity, lipid peroxidation, and nitric oxide in postmenopausal osteoporosis - Ozgocmen, Salih; Kaya, Huseyin; Fadillioglu, Ersin; Yilmaz, Zumrut (Elsevier Science Inc, 2007)
Background. The aims of this study were to compare erythrocyte antioxidant enzyme activities, lipid peroxidation, and nitric oxide levels (NO) in women with postmenopausal osteoporosis (PMO) and non-porotic postmenopausal healthy controls and to assess the relationship between bone mineral density and these oxidant/antioxidant parameters. Additionally, in vivo effects of three different anti-osteoporotic drugs, calcitonin, risedronate and raloxifene, on the erythrocyte oxidant-antioxidant status in women with PMO were also assessed. Methods. Postmenopausal women aged 40-65 years and without previous diagnosis or treatment for osteoporosis and independent in activities of daily living were included. Bone mineral density was measured at the lumbar spine and proximal femur using DXA. Erythrocyte enzyme activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), and lipid peroxidation end-product malondialdehyde (MDA) and nitrite/nitrate levels, by product of NO, were assessed. Fifty-nine women with PMO were included (mean age 56.7 years), 44 completed course of therapy and were analyzed. Twenty-two non-porotic healthy women (mean age 55.8 years) were included as controls. Results. Patients had significantly lower CAT and GSH-Px enzyme activity and higher levels of MDA and NO than non-porotic healthy controls. Proximal femur BMD measurements significantly correlated with NO levels. QUALEFFO scores improved in different levels with these short-term treatments. In all treatment groups, erythrocyte MDA levels significantly decreased; moreover, risedronate reduced NO levels and raloxifene enhanced CAT enzyme activity. Conclusions. Oxidative stress plays an important role in the pathogenesis of PMO. Studied drugs had ultimate effects on reducing lipid peroxidation. Raloxifene also had potent effects in the enhancement of antioxidant defense system. (c) 2007 IMSS. Published by Elsevier Inc.
Keywords: postmenopausal osteoporosis; calcitonin; risedronate; raloxifene; antioxidant enzyme; nitric oxide